PREPARATION AND APPLICATION OF COLORED ANTIBACTERIAL COTTON FIBER BASED ON MICROSTRUCTURAL CONTROL (Conferencea, 2022)
Increasing competition in the world market of textile products increases the necessity of reducing wholesale prices due to the development of production technologies in the countries producing textile raw materials, to further improve the consumer characteristics of the product and reduce the production costs. Accordingly, in order to improve the quality of products produced in the field of textiles and light industry in the world market and reduce their cost, it is necessary to identify and eliminate factors that negatively affect product quality at all stages of production, as well as in the spinning process, to create resource-efficient, automated technologies that reduce product production costs and to implement them. implementation is of great importance.